Intellectual extremism of some political Islam parties in The Middle East - Mohammad S. Alkhazaleh, Rakan R. Alhrahsheh, (Opción, 2019)
This study aims to identify the extremism ideology of some political Islam groups in the Arab world. The historical approach and content analysis methodology were used to recognize the history, objectives and impacts of such groups on society. As a result, the extremist ideology of the groups was caused by their ignorance of the appropriate methods to transfer the Qur'an and Sunnah. It is also concluded that the mercenaries who do not have specific interests in life are most members of extremist groups.